Perspectives on future climate research: a preface to the special collection from the World Climate Research Programme 2023 Open Science Conference - Stammer, Detlef; Cleugh, Helen (Frontiers in Climate, 2025)
Since its inception in 1980, the World Climate Research Programme (WCRP) has coordinated and facilitated international climate research to develop, share, and apply the climate knowledge that contributes to societal well-being. Through international science coordination and partnerships, WCRP contributes to advancing our understanding of the multi-scale dynamic interactions between natural and social systems that affect climate. WCRP-supported research builds the climate science that is the basis for IPCC Assessments and Special Reports and underpins the United Nations Framework Convention on Climate Change including national commitments to the 2015 Paris Agreement. It also contributes to the knowledge that supports the 2030 Agenda for Sustainable Development, the Sendai Framework for Disaster Risk Reduction, and multilateral environmental conventions. To shape the future climate science agenda, WCRP organized its second Open Science Conference, which took place between October 23 and 27, 2023 and was hosted by the Rwanda Environment Management Authority (REMA) in Kigali, Rwanda. This once-in-a-decade event took place in a truly hybrid setting, bringing together over 1,400 participants representing scientists from diverse research communities worldwide as well as practitioners, planners, and politicians.